Suitability of Brahmi (Bacopa monnieri L.) cultivation on fly ash-amended soil for better growth and oil content. Issue 1 (2nd January 2021) - Panda, Debabrata; Barik, Jyoti R.; Barik, Jijnasa; Behera, Prafulla K.; Dash, Debasis
Abstract: Sustainable application of fly ash and its management in agriculture is a major challenge nowadays. A pot culture experiment was conducted to find out the most suitable level of fly ash application for soil amendments that can improve the plant growth and productivity of Brahmi ( Bacopa monnieri L.). After growing seedlings of B. monnieri under different levels of fly ash for 90 days, a significant increase in plant biomass, essential oil content and tolerance index (more than 100%) was observed under 25% of fly ash amended soil in comparison to garden soil and higher fly ash treatments. Leaf chlorophyll content and photosynthetic parameters were remained unchanged under 25% of fly ash as compared to seedlings grown on garden soil. However, these parameters were significantly declined under higher concentrations of fly ash treatments. Higher levels of fly ash caused oxidative damage and the induction of some antioxidative enzymes activities in B. monnieri indicates its capability to endure oxidative stress tolerance. Overall, our study showed that 25% of fly ash can be used as soil amendment for cultivation of B. monnieri L. leading to enhance plant biomass and essential oil production.